(untitled) (Alternautas, 2022)
Weaving Solidarity (2022) by Sebastian Garbe is a novel and potent contribution to debates on international solidarity and decoloniality. The thread that connects the book’s different chapters is the author’s examination of how the Mapuche, as a transnational and collective actor composed by the Mapuche living in the Indigenous territory of Wallmapuand the Mapuche diaspora living in Europe, produce their own network of solidarity. Contrary to analyses that interpret relations of solidarity in a humanitarian key, i.e. analyses that make a clear distinction between passive receivers of support who are affected by a particular conflict and active agents (external to the conflict) whose moral imperative is to give support, Garbe shows how the Mapuche are not mere receptors of solidarity. On the contrary, the Mapuche themselves have created a design of transnational solidarity since the 1970s, which has neither been fully determined by non-Indigenous givers of support located in the global north, nor fully occupied or saturated by “the conflict” with the Chilean state.